2017
DOI: 10.1038/nutd.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide reduces body weight by upregulation of adenylate cyclase 3

Abstract: Objective:According to recent studies, adenylate cyclase 3 (AC3) is associated with obesity. Liraglutide reduces blood glucose levels and body weight (BW). We performed a 2 × 2 factorial experiment to study the relationships among AC3, liraglutide and obesity and to obtain a more comprehensive understanding of the mechanisms underlying the physiological effects of liraglutide on obesity.Methods:A high-fat diet was used to induce obesity in C57BL/6J mice. Both the normal and obese mice were treated with liraglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…5f ), indicating that α-cedrene affects the protein expression of Adcy3 and PKA Cα in an OR10J5-dependent manner. This finding is in line with the recent reports indicating that protein levels of Adcy3 36 , 37 and PKA Cα 38 was upregulated in response to agonist-induced stimulation of a GPCR in mouse liver tissue and bone marrow stromal cells, respectively. Nevertheless, it remains to be determined how α-cedrene that acts through OR10J5 impacts Adcy3 and PKA Cα expression.…”
Section: Discussionsupporting
confidence: 93%
“…5f ), indicating that α-cedrene affects the protein expression of Adcy3 and PKA Cα in an OR10J5-dependent manner. This finding is in line with the recent reports indicating that protein levels of Adcy3 36 , 37 and PKA Cα 38 was upregulated in response to agonist-induced stimulation of a GPCR in mouse liver tissue and bone marrow stromal cells, respectively. Nevertheless, it remains to be determined how α-cedrene that acts through OR10J5 impacts Adcy3 and PKA Cα expression.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, treatment with a GLP‐1R agonist, prescribed to improve glycaemic control in patients with type 2 diabetes, leads to reduced body weight and reduced insulin resistance combined with up‐regulated hepatic levels of Adcy3 mRNA and protein in diabesity and obese mice . These observations fit with the observation of weight‐reducing properties of GLP‐1R‐agonist treatment in patients with type 2 diabetes , which thus might be explained, at least partly, by ADCY3 activation.…”
Section: Genetic Association Studies Of Metabolic Traits In Isolated supporting
confidence: 65%
“…We recently showed that chronic ghrelin administration for 4 weeks postpones R6/2 mouse weight loss by one week 38 . Administration of the GLP-1 analogue, liraglutide, has been shown to be associated with weight loss 22 , 39 , which could be problematic if used in a mouse model displaying weight loss, such as the R6/2 mouse. However, we here demonstrate that daily injections of either liraglutide alone or together with ghrelin for 2 weeks (from 10 to 12 weeks of age) did not further decrease body weight in R6/2 mice.…”
Section: Discussionmentioning
confidence: 99%